AHARA VICHARA: AYURVEDIC CONCEPT OF DIET - R., Borakhade Vasundhara; Rokade, Reshma (International Journal of Research -GRANTHAALAYAH, 2018)
Ahara is the most important factor in life. Health as well as disease is dependent on ahara. Proper diet, taken in proper manner can lead to better health or else can lead to diseases. Food is the source of life, strength, complexion and Oja of living beings. Food in turn, derives its properties from six primary tastes which are inherent in the substances that comprise food. The substances, their specific tastes, qualities, potencies and digestive transformations are responsible for equilibrium of the Dosha and Dhatu. As growth, strength, good health, complexion and the alertness of senses are traceable to food and its inequality causes illness. Diet therapy is a broad term for the practical application of the concept of nutrition as a preventive or corrective treatment of diseases. It comprises food prescribed, regulated or restricted in kind and amount for therapeutic and other purposes. This usually involves the modification of an existing dietary lifestyle to promote optimum health. However, in some cases, an alternative dietary lifestyle plan may be developed for the purpose of eliminating certain foods in order to reclaim health. Diet therapy provides an outline regarding which kind of food to eat and which to avoid. Ayurvedic principles are concerned about every part of the body, mentally and physically through diet.